2017
DOI: 10.3390/cryst7030067
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal Growth of Multiferroic Double Perovskites: Yb2CoMnO6 and Lu2CoMnO6

Abstract: Abstract:We report on the growth of multiferroic Yb 2 CoMnO 6 and Lu 2 CoMnO 6 single crystals which were synthesized by the flux method with Bi 2 O 3 . Yb 2 CoMnO 6 and Lu 2 CoMnO 6 crystallize in a double-perovskite structure with a monoclinic P2 1 /n space group. Bulk magnetization measurements of both specimens revealed strong magnetic anisotropy and metamagnetic transitions. We observed a dielectric anomaly perpendicular to the c axis. The strongly coupled magnetic and dielectric states resulted in the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The dominant FIM order between Er 3+ and FM Co 2+ /Mn 4+ sublattices was identified by compensated magnetization ( M ) occurring at T Comp = 3.15 K. From our precise measurement of isothermal M in the low T regime, the inversion of the magnetic hysteresis loop was observed below T Comp , which can be explained by the delicate balance between different magnetic moments, and qualitatively by an extended Stoner–Wohlfarth model 3538 . The ferroelectric polarization ( P ) and dielectric constant ( ε ′) measurements demonstrated an additional inclusion of the MF phase as found in Yb 2 CoMnO 6 and Lu 2 CoMnO 6 23,24 . Associated with the coexistence of FIM and MF phases, the disappearance of MF phase by an external H occurs simultaneously with the metamagnetic transition, revealing exclusive characteristics of the double perovskite.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The dominant FIM order between Er 3+ and FM Co 2+ /Mn 4+ sublattices was identified by compensated magnetization ( M ) occurring at T Comp = 3.15 K. From our precise measurement of isothermal M in the low T regime, the inversion of the magnetic hysteresis loop was observed below T Comp , which can be explained by the delicate balance between different magnetic moments, and qualitatively by an extended Stoner–Wohlfarth model 3538 . The ferroelectric polarization ( P ) and dielectric constant ( ε ′) measurements demonstrated an additional inclusion of the MF phase as found in Yb 2 CoMnO 6 and Lu 2 CoMnO 6 23,24 . Associated with the coexistence of FIM and MF phases, the disappearance of MF phase by an external H occurs simultaneously with the metamagnetic transition, revealing exclusive characteristics of the double perovskite.…”
Section: Introductionmentioning
confidence: 75%
“…Recently, new magnetism-driven ferroelectrics, i.e. type-II multiferroics, were found in double-perovskite Yb 2 CoMnO 6 and Lu 2 CoMnO 6 23,24 . The initial polycrystalline analysis of neutron diffraction and bulk electric properties for Lu 2 CoMnO 6 suggested that the ferroelectricity arises from the symmetric exchange striction of the ↑↑↓↓ spin chains with alternating Co 2+ and Mn 4+ charge valences 48 , consistent with the Ising spin chain magnet of Ca 3 CoMnO 6 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, double‐perovskite R 2 CoMnO 6 (R = La, …, Lu) compounds have been studied due to their fascinating functional properties like magnetocaloric effect, exchange bias effect, and multiferroicity, arising from intricate magnetic phases and interactions. In these compounds, the incomplete exchange between Co 2+ and Mn 4+ ions naturally engenders anti‐sites of ionic disorders and/or antiphase boundaries.…”
mentioning
confidence: 99%
“…The formation of the additional AFM clusters by the anti‐sites is the known reason for the observed magnetic exchange bias in polycrystalline Y 2 CoMnO 6 . Yb 2 CoMnO 6 and Lu 2 CoMnO 6 present multiferroicity due to the cooperative O 2− displacements through symmetric exchange strictions in the up‐up‐down‐down (↑↑↓↓) spin configuration . Thus, comprehensive investigation of ionic orders and versatile magnetic interactions is crucial for understanding the intrinsic characteristics in double perovskites.…”
mentioning
confidence: 99%